Applications of numerical simulation to the sedimentation in the Sanmenxia reservoir and the Lower Yellow River. (2nd August 2010) - Hu, Chunhong; Guo, Qingchao; Chen, Jianguo; Cao, Wenhong
The non-harmonious combination of insufficient water and excessive sediment causes many problems for the Yellow River. These problems include severe sedimentation in the Sanmenxia reservoir, the rising of the water level at Tongguan for a given discharge (1000 m³/s) and the rising of the bed level of the Lower Yellow River (LYR). How to lower the Tongguan Water Level (TGWL) and alleviate sedimentation in the LYR has become one of the most important issues in managing the Yellow River. This paper provides a summary of recent studies by authors on solving these key sediment problems in the Yellow River.